Use of physical and chemical methods to overcome dormancy in Mouriri cearensis Huber seeds (Research, Society and Development, 2023)
Dormancy is the process in which one or more blocking mechanisms limit seed germination, requiring external stimuli. Mouriri cearensis Huber, popularly known as “manipuçá”, is an endemic and native species of Brazil, with confirmed occurrences only in the North and Northeast of Brazil. The objective of the present work was to evaluate different physical and chemical methods to overcome the dormancy of Mouriri cearensis seeds. To overcome dormancy, M. cearensis seeds were subjected to the following pre-germination treatments: control; fragmentation; sandpaper; fragmentation + GA3; sandpaper + GA3; H2O/24 h; H2O/48 h; substrate with GA3; substrate with KNO3; immersion in GA3; immersion in KNO3; immersion in H2O; and scarification in H2SO4. The following parameters were evaluated: germination test, first count, germination speed index, radicle and seedling lengths, fresh weight and dryness of the radicle and seedling. The most efficient methods to overcome manipuçá seed dormancy were treatments with fragmentation, fragmentation + GA3 and mechanical scarification with sandpaper nº 80. It is worth mentioning that it is necessary to carry out more studies on the germination of species of the genus Mouriri, aiming to know the germination process, preserve the species and produce seedlings.